Caleidoscópio, narrativas e subjetividade na arqueologia pública - Fernando Alexandre Soltys (2010)
This dissertation examined the relation between the archaeological theories and how they construct narratives, and how each of these lines of thought relates to the public in different contexts: Media, Museums, and the Archaeologists themselves. In an interpretative perspective, I discuss how the institutions and the relation with the public is today, putting the insufficiencies of the traditional forms of knowledge creation in the contemporary world.